PENGEMBANGAN BAHAN AJAR INTERAKTIF UNTUK PEROLEHAN KETERAMPILAN MENENTUKAN LUAS DAERAH PADA MATERI INTEGRAL - Arizal Arizal; Dede Suratman; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract A lot of educators who are still using the conventional materials, i.e., instant, and without efforts to plan, prepare, and organize themselves. So, it’s risk is very possible if the learning materials they use are not contextual, not interesting, boring, and not in accordance with the needs of students. The method used was the research and development method. The results of this research, The interactive learning material developed was feasible. Because this learning material was stated to be very valid and feasible by experts even though it has a slight disadvantage. The learning material was able to increase students' skills. After using its, 95.65% of 23 students have intellectual skills in solving questions about daily life related to the area in the integral, 86.96% can find the intersection of the two curves that intersect and determine the area that is limited by the interval and determine the area of the area limited by the intersection of the two curves. For physical skills, 86.96% of 23 students can describe the area to be searched for if it is limited by the curve. Keywords: Area, Development, Interactive Teaching Materials, Skills